Natural Antioxidants Effect of Mulberry Fruits (Morus nigra and Morus alba L.) On Lipids Profile and Oxidative Stress in Hypercholestrolemic Rats - Mahmoud, Mohamed Y. (Pakistan Journal of Nutrition, 2013)
Mulberry belongs to the Morus genus of the Moraceae family. There are 24 species of Morus, with at least 100 known varieties. Mulberry leaves, bark and branches have long been used in Chinese medicine. In most European countries mulberries are grown for fruit production. Mulberry are a good source of polyphenols, especially anthocyanins and micronutrients. In epidemiological and clinical studies, these constituents have been associated with improved cardiovascular risk profiles. Human intervention studies using (either fresh, or as juice, or freeze-dried), or purified anthocyanin extracts have demonstrated significant improvements in LDL oxidation, lipid peroxidation, total plasma antioxidant capacity, dyslipidemia and glucose metabolism. Benefits were seen in healthy subjects and in those with existing metabolic risk factors. The present study was performed to determine the natural antioxidants content of black and white mulberry fruits (Morus nigra and Morus alba L.) in Egypt and study the effects of different levels different levels of black and white mulberry fruits on lipid profile and oxidative stress in hypercholestrolemic rats. Forty adult male albino rats Sprague Dawley strain with an average weight of (100±120 g) randomly divided into 8 groups (each of 5 rats), Group 1: Control negative, rats fed on basal diet, Group 2: Control positive, rats fed on hypercholesterolemic diet composed of basal diet +2% cholesterol. Others groups (3-8), rats fed on hypercholestrolemic diet supplemented by different levels of black or white mulberry dry fruits (2.5, 5 and 10%) for four weeks. Results observed that rats fed on hypercholestrolemic diet without supplementation (control positive) had significant increase in malonaldhyde (MDA), nitric oxide (NO), total cholesterol, triglycerides (T.G), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) while it had significant decrease in total antioxidant capacity (TAC) and high density lipoprotein (HDL) comparing with rats fed on basal diet (control negative). Moreover, The group administrated with Morus nigra L. 10% had lowest value in malonaldhyde (MDA) and nitric oxide (NO) followed by the group administrated with Morus alba L. 10%. In addition, all hypercholestrolemic groups administrated with different levels (2.5, 5 and 10%) of black and white mulberry fruits (Morus nigra and Morus alba L.) had significant increase in total antioxidant capacity (TAC). The group administrated with Morus nigra L. 10% had highest value in total antioxidant capacity (TAC) followed by the group administrated with Morus alba L. 10%. In addition, all hypercholestrolemic groups administrated with different levels (2.5, 5 and 10%) of black and white mulberry fruits (Morus nigra and Morus alba L.) had significant decrease in total cholesterol, triglycerides (T.G), low density lipoprotein (LDL) and very low density lipoprotein (VLDL). and significant increase in high density lipoprotein (HDL),comparing with rats fed on hypercholestrolemic diet (control positive). It concluded that, consumption of black and white mulberry fruits (Morus nigra and Morus alba L.) my modify the risk of hypercholesterolemia and it have more potential as a health supplement rich in natural antioxidants. Moreover, mulberries are emerging as a dietary source of multiple compounds and nutrients, including anthocyanins, flavonoids, vitamins and fiber, that reduce CVD risk. While limited epidemiological data inversely associate consumption of berries with inflammation and CVD, these conclusions need to be strengthened in future case-control or cohort studies investigating the long-term health benefits of berries in specific populations.